Systematic theology - Tillich, Paul, 1886-1965 (University of Chicago Press, 1971)
In this volume, the second of his three-volume reinterpretation of Christian theology, Paul Tillich comes to grips with the central idea of his system-the doctrine of the Christ. Man's predicament is described as the state of "estrangement" from himself, from his world, and from the divine ground of his self and his world.